Science Literacy Competency Profile of Science Education Students in Understanding the Concept of Thermodynamics - Rif'atul Himmah; Budi Jatmiko; Binar Kurnia Prahani; Iqbal Ainur Rizki (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: This study aimed to analyze the science literacy competency profile of science education students in understanding thermodynamics concepts at the State University of Surabaya, with a specific focus on identifying competency levels and gender differences in science literacy achievement. Method: A quantitative descriptive research was conducted involving 35 students from Science Education Class B, selected through random sampling. Data collection was conducted using a science literacy test instrument adapted from the 2025 PISA framwork, consisting of 15 questions (10 multiple choice and 5 essay question) designed to measure three primary science compenties. Results: The analysis revealed that 51.42% of students achieved a proficient level, 28.58% reached an advanced level, and 20% were at a basic level. Students showed the highest competency in explaining scientific phenomena (74.4%), followed by constructing and evaluating scientific investigations (65.7%), and lowest in research and scientific information used for decision-making (60.6%). Female students exhibited slightly better performance, with a 4-point advantage over their male counterparts. Novelty: This study provides a detailed analysis of science literacy competencies in understanding thermodynamics among pre-service science teacher. It also incorporates the lates 2025 PISA framework and highlights gender-based performance differences. The findings provide valuable insights for developing targeted interventions in science teacher education programs, particularly in strengthening evidence-based decision-making skills and practical applications of thermodynamics concepts.